Pancasila Character Education for Millennials in Higher Education: The Future Challenges for Indonesia in Global Prespective - Nur Jannatul Khoirina; Faqih Hakim Al-Majiid; Keylie Alisah Great (Jurnal Panjar: Pengabdian Bidang Pembelajaran, 2022)
Globalization is a global process with all the speed of change and rapid technological development. The current of globalization brings many positive impacts. All forms of cultural, language and news information can be spread very quickly through offline and online media in the era of globalization. But besides the positive impact, there are also negative impacts. Among them are many generations of people who are influenced by western culture that are not in accordance with national culture, the spread of hoaxes that contain false news, to the occurrence of moral crises. Pancasila character education is an effort to cultivate character based on the practice of the principles of the Pancasila which gives noble values ​​to the attitudes and behavior of each individual. Pancasila as a guideline for Indonesian citizens should be practiced properly in daily life. Millennials live in an era of globalization with the sophistication of digital technology. They are used to all digital convenience access. But it cannot be denied that the moral crisis has hit the millennial generation. This can be seen from the rise of cases of sexual harassment, murder, and theft by students who in fact are millennial generations in universities. The purpose of the research in this article is to analyze the important role of character education based on Pancasila in facing the challenges of globalization towards millennial generations in universities.